2020
DOI: 10.1111/ane.13299
|View full text |Cite
|
Sign up to set email alerts
|

Types of occult cancer in stroke and the relation to smoking

Abstract: Almost three percent of patients admitted with acute stroke in Denmark harbor occult cancer which will become manifest within a year after stroke. It is 50% more than in the general population without stroke. 1 The risk for harboring occult cancer in stroke patients, therefore, is a matter of concern. It was recently shown that patients with newly diagnosed cancers had previously suffered a stroke twice as often if cancers were related to smoking (eg, cancers of the lung, colon, etc) while this was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Therefore, more efficient screen method for example positron emission tomography-computed tomography (PET-CT) might contribute to early detection of primary tumor. Clinicians need to be vigilant when they encounter patients who manifest as internal diseases such as stroke [ 6 , 7 , 8 , 9 ], thromboembolism [ 10 , 11 ] and dermatomyositis [ 12 ]. As occult NSCLC might be the fundamental cause of these non-cancer-related symptoms, the more refined examinations should be performed as soon as possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, more efficient screen method for example positron emission tomography-computed tomography (PET-CT) might contribute to early detection of primary tumor. Clinicians need to be vigilant when they encounter patients who manifest as internal diseases such as stroke [ 6 , 7 , 8 , 9 ], thromboembolism [ 10 , 11 ] and dermatomyositis [ 12 ]. As occult NSCLC might be the fundamental cause of these non-cancer-related symptoms, the more refined examinations should be performed as soon as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Occult lung cancer, defined as the presence of malignant tumor cells in bronchial washing or sputum but demonstrated no tumor evidence by imaging [ 1 , 2 ], often manifests as metastasis diseases [ 3 , 4 , 5 ] or other internal diseases such as stroke [ 6 , 7 , 8 , 9 ], venous thromboembolism [ 10 , 11 ] and dermatomyositis [ 12 ]. When these patients develop apparent non-cancer-related symptoms, the vast majority may have already progressed to an advanced stage.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 13 15 Solid tumors in advanced stage disease of the lung, pancreatic, and colorectal cancers seem to carry the highest stroke risk. 4 , 11 , 16 Other studies reported high incidence of stroke in breast and prostate cancer. 3 , 9 ( Box 1 ) A vast increase in stroke risk is also seen in metastatic disease, indicating a more advanced disease.…”
Section: Association Between Cancer and Different Subtypes Of Strokementioning
confidence: 99%
“… 3 , 9 ( Box 1 ) A vast increase in stroke risk is also seen in metastatic disease, indicating a more advanced disease. 15 Stroke can be the initial presentation of cancer 16 or follow a cancer diagnosis, however, 13 and the risk of stroke remains elevated even over 10 years following cancer diagnosis. 15 …”
Section: Association Between Cancer and Different Subtypes Of Strokementioning
confidence: 99%
See 1 more Smart Citation